Landscape heterogeneity buffers biodiversity of simulated meta-food-webs under global change through rescue and drainage effects - Remo Ryser (Nature Portfolio, 2021)
Habitat fragmentation and eutrophication have strong impacts on biodiversity but there is limited understanding of their cumulative impacts. This study presents simulations of meta-food-webs and provides a mechanistic explanation of how landscape heterogeneity promotes biodiversity through rescue and drainage effects.